The Effects of Olive Leaf Extract Administration on the Cerebral Hypoperfusion-Induced Electrophysiological Alterations in Rat Heart - Mehrnoush Moghaddasi; Majid Taati; Hasan Noroozi; Sam Bamani Lirgeshasi; Soheila Pourkhodadad; Bahram Delfan; Afshin Nazari * (Herbal Medicines Journal, 2017)
Background and Aim: In the present study, the role of ethanolic extract of olive (Olea europaea) leaf administration against the cerebral hypoperfusion-induced electrophysiological alterations and left ventricular thickness in rat heart was studied.